1997
DOI: 10.3109/08916939709003854
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity to Ryanodine Receptor and Titin in Myasthenia Gravis is Associated with GM Allotypes

Abstract: Myasthenia gravis (MG) is mediated by autoantibodies against the acetylcholine receptor at the muscle endplate. Some MG patients have in addition antibodies (Ab) to the skeletal muscle proteins ryanodine receptor (RyR) and titin. We have examined GM and KM allotypes, RyR and titin Ab in 44 MG patients (37 thymoma patients and 7 non-thymoma, late-onset patients) and 292 non-MG controls to see if GM/KM allotypes associate with differences in autoantibody production. All patients had titin Ab, and 15 thymoma pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
9
1
Order By: Relevance
“…In all subgroups of MG patients (MGT, MGH and MGN), the frequency of titin antibodies is highest in MGT (76 %), increasing up to 95 % of MG patients with epithelial predominant-thymoma. The levels of titin antibodies in our MGT were 80 %, similar to that found in other studies [6,13,16]. Nearly 34 % of MGN [4,20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In all subgroups of MG patients (MGT, MGH and MGN), the frequency of titin antibodies is highest in MGT (76 %), increasing up to 95 % of MG patients with epithelial predominant-thymoma. The levels of titin antibodies in our MGT were 80 %, similar to that found in other studies [6,13,16]. Nearly 34 % of MGN [4,20].…”
Section: Discussionsupporting
confidence: 91%
“…The myoid cells of thymus contain both titin mRNA and titin itself. Titin epitopes and mRNA containing the MIR and N2-line regions of titin are expressed in neoplastic epithelial cells in thymoma [13]. In medullary and mixed thymoma, and especially in normal thymus, immunoreactivity to titin antibodies is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no strong HLA associations in thymoma MG patients, but genetic factors are known to be important [61,62]. Associations with Ig heavy-chain genetic markers including GM pheno-and allotypes as well as with a FckRIIA subtype and certain tumor necrosis factor (TNF)-h T1 and TNF-i 2 alleles have been shown for titin-antibody-positive MG patients with thymoma [63][64][65][66]. This suggests that only thymoma patients with a certain immunogenetic makeup will develop MG and titin antibodies.…”
Section: Induction Of the Immune Response Against Titinmentioning
confidence: 99%
“…For the IIM, GM and KM associations have been described in both Mesoamerican and Korean populations (10, 11). While the physiologic mechanisms underlying these associations remain uncertain, several studies have identified higher serum titers of specific subclasses of IgG antibodies (i.e., IgG1, IgG2, IgG3) directed against antigenic epitopes of infectious disease agents or self proteins in persons with specific GM and KM markers (1218). In an effort to understand if these immune response genes may be important in the pathogenesis of myositis, we have performed a comprehensive examination of GM and KM markers in a large population of European American (EA) (n=514) and African American (AA) (n= 123) adult and juvenile IIM patients representing the major clinicopathologic and autoantibody subgroups.…”
mentioning
confidence: 99%